On-Target Anti-TGF-β Therapies Are Not Succeeding in Clinical Cancer Treatments: What Are Remaining Challenges? - Teixeira, Adilson Fonseca; ten Dijke, Peter; Zhu, Hong-Jian (Frontiers in Cell and Developmental Biology, 2020)
Metastasis is the leading cause of death for cancer patients. During cancer progression, the initial detachment of cells from the primary tumour and the later colonization of a secondary organ are characterized as limiting steps for metastasis. Epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) are opposite dynamic multistep processes that enable these critical events in metastasis by altering the phenotype of cancer cells and improving their ability to migrate, invade and seed at distant organs. Among the molecular pathways that promote tumorigenesis in late-stage cancers, transforming growth factor-β (TGF-β) is described as an EMT master inducer by controlling different genes and proteins related to cytoskeleton assembly, cell-cell attachment and extracellular matrix remodelling. Still, despite the successful outcomes of different TGF-β pharmacological inhibitors in cell culture (in vitro) and animal models (in vivo), results in cancer clinical trials are poor or inconsistent at least, highlighting the existence of crucial components in human cancers that have not been properly explored. Here we review most recent findings to provide perspectives bridging the gap between on-target anti-TGF- therapies in vitro and in pre-clinical models and the poor clinical outcomes in treating cancer patients. Specifically, we focus on (i) the dual roles of TGF-β signalling in cancer metastasis; (ii) dynamic signalling; (iii) functional differences of TGF-β free in solution versus in exosomes; (iv) the regulatory effects of tumour microenvironment (TME) – particularly by cancer-associated fibroblasts – on TGF-β signalling pathway. Clearly identifying and establishing those missing links may provide strategies to revitalise and clinically improve the efficacy of TGF-β targeted therapies.